Surface EMG multichannel array using active dry sensors for forearm signal extraction - Reátegui, J.; Callupe, R. (Institute of Electrical and Electronics Engineers, 2017)
Although superficial electromyographic signals are the most common input signal for machine learning algorithms in hand gesture recognition and finger force estimation applications, there are only a few commercially available systems for superficial EMG acquisition. This work proposes a cheap and easy to fabricate, dry superficial electrodes array. This system uses multiple active differential sensors integrated in a small double layer PCBs, each one uses two small rectangle areas of the bottom layer as conductive layer for signal acquisition. With a differential gain of 60dB between 23 and 3000Hz and a common mode rejection ration of -60dB at 60Hz. Design criteria and simulations are presented.
Keywords: Rectangle; SIGNAL (programming language); Computer science; Common-mode signal; Layer (electronics); Electronic engineering; Acoustics; Engineering; Computer hardware; Materials science; Analog signal; Mathematics; Digital signal processing; https://purl.org/pe-repo/ocde/ford#2.02.00